Autosomal recessive IFT57 hypomorphic mutation cause ciliary transport defect in unclassified oral–facial–digital syndrome with short stature and brachymesophalangia. Issue 6 (29th April 2016) - Thevenon, J.; Duplomb, L.; Phadke, S.; Eguether, T.; Saunier, A.; Avila, M.; Carmignac, V.; Bruel, A.‐L.; St‐Onge, J.; Duffourd, Y.; Pazour, G.J.; Franco, B.; et al.
Abstract : Abstract : The 13 subtypes of oral–facial–digital syndrome (OFDS) belong to the heterogeneous group of ciliopathies. Disease‐causing genes encode for centrosomal proteins, components of the transition zone or proteins implicated in ciliary signaling. A unique consanguineous family presenting with an unclassified OFDS with skeletal dysplasia and brachymesophalangia was explored. Homozygosity mapping and exome sequencing led to the identification of a homozygous mutation in IFT57, which encodes a protein implicated in ciliary transport. The mutation caused splicing anomalies with reduced expression of the wild‐type transcript and protein. Both anterograde ciliary transport and sonic hedgehog signaling were significantly decreased in subjects' fibroblasts compared with controls. Sanger sequencing of IFT57 in 13 OFDS subjects and 12 subjects with Ellis–Van Creveld syndrome was negative. This report identifies the implication of IFT57 in human pathology and highlights the first description of a ciliary transport defect in OFDS, extending the genetic heterogeneity of this subgroup of ciliopathies.